Flexible adaptation planning for water sensitive cities. (August 2018) - Radhakrishnan, Mohanasundar; Pathirana, Assela; Ashley, Richard M.; Gersonius, Berry; Zevenbergen, Chris
Abstract: Cities have started adapting to uncertain climate drivers such as temperature and sea level rise, and some cities are also transitioning towards concepts such as Water Sensitivity. In adaptation planning, flexibility is considered as an important characteristic to respond to changing circumstances. This paper develops a novel approach to identify where flexibility can best be embedded in urban flood risk management systems. The identification of a flexible water sensitive adaptation response is based on change propagation; i.e. the response's ability to minimise negative or maximise positive impacts in urban systems . The Flexible adaptation planning process (WSCapp), comprising change propagation – especially how positive and negative impacts propagate in an urban environment, can be used by those concerned with urban planning and urban adaptation to identify " where " the flexible adaptation responses can be implemented. WSCapp can be used to decide the type of adaptation response such as changes to streetscape, place making or architectural forms that can best contribute towards the objectives of a water sensitive city. Highlights: Flexibility is an essential characteristic of urban planning to deal with uncertainties. Flexible agile adaptation process (WSCapp) identifies ' where ' flexibility can be built in urban systems. The approach is inspired by the flexible product platform design processes prevalent in the automobile sector. WSCapp is based on change propagation, i.e., how negative impacts reduce and positive impacts increase in the system. WSCapp can make urban adaptation agile, i.e. quickly adapt, and enable planners to identify the most flexible responses.